The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1111/j.1365-2796.1991.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous colitis: a prospective trial of prednisolone in six patients

Abstract: In a prospective study, the clinicopathological effect of prednisolone was evaluated in six patients with collagenous colitis. Prednisolone was associated with a significant decrease in stool frequency. However, the effect was transitory, since the diarrhoea recurred when prednisolone treatment was discontinued. There was a trend toward a diminished inflammatory response in the post-treatment biopsies, but the thickness of the collagen band remained unchanged, except in one patient. Until the results of furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…The effects of corticosteroids on eosinophils are several, including diminished recruitment, downregulation of activation, enhanced eosinophil apoptosis, and increased tissue eosinophil clearance. [51][52][53] A previous prospective study on 6 CC patients reports a reduction in the numbers of eosinophils after oral prednisolone treatment, 54 in line with our results. We also revealed that eosinophil activation is down-regulated after 8 weeks of budesonide treatment.…”
Section: Discussionsupporting
confidence: 94%
“…The effects of corticosteroids on eosinophils are several, including diminished recruitment, downregulation of activation, enhanced eosinophil apoptosis, and increased tissue eosinophil clearance. [51][52][53] A previous prospective study on 6 CC patients reports a reduction in the numbers of eosinophils after oral prednisolone treatment, 54 in line with our results. We also revealed that eosinophil activation is down-regulated after 8 weeks of budesonide treatment.…”
Section: Discussionsupporting
confidence: 94%
“…Collagenous colitis is unrelated to other forms of inflammatory bowel disease, such as chronic ulcerative colitis and Crohn's disease, and it requires a different patient management [7,20], although some evidence exists about transitions from collagenous colitis towards ulcerative colitis and from lymphocytic colitis to collagenous colitis. Hence, correct diagnosis is of clinical importance for identifying the cause of the clinical symptoms and to avoid inappropriate (over)treatment [18]. However, in cases that do not show pronounced subepithelial band formation, histological diagnosis is difficult and sometimes inconclusive.…”
Section: Discussionmentioning
confidence: 97%
“…The following treatment schedules have so far been tried with little success or conflicting results: 5-ASA, sulfasalazine, metronidazole, mepacrine, cholestyramine and non-specific antidiarrheal medications [4,5,9,10]. Prednisone seems to be associated with a better clinical response [5,11], but toxicity is a major concern. In this small study, complete and partial responses to budesonide therapy in collagenous colitis were observed in 3 and 2 of the 5 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%